Design and Implementation of Riverbed Modeler M&S Framework for Multi-Layered Future Tactical Networks with Intelligent SDN Control Architecture - Lee, Cheol Woong; Lee, Gyu Min; Lee, Hojin; Roh, Byeong Hee (Journal of Korean Institute of Communications and Information Sciences, 2022)
Software Defined Networking (SDN) divides the network functions into control and data planes so that a controller in the control plane can dynamically control the operations of switches in the data plane. Efforts to adopt the SDN structure for tactical networks composed of heterogeneous and complex devices and systems are being made. Since tactical networks have multi-layered complex structures, it is not easy to construct Modeling and Simulation (M&S) environments supporting SDN structure. This paper proposes an M&S framework for multi-layered future tactical networks employing intelligent SDN control architectures. As an M&S tool, we utilize Riverbed Modeler, which is widely used and proven for tactical network performance analysis. The proposed M&S framework is implemented, and the experimental results show its effectiveness.
Keywords: Future Tactical Network; Modeling and Simulation; Multi-layered Atchitecture; Riverbed Modeler; Software Defined Networking